Japan's Inbound Tourism Boom : Lessons for its Post-COVID-19 Revival - Nguyen, Anh Thi Ngoc. (Washington, D.C. : International Monetary Fund, 2020)
In this paper, we review developments in Japanese inbound tourism and investigate the main determinants of its rapid growth prior to the COVID-19 pandemic. Using a panel autoregressive distributed lag (ARDL) model with data on 34 tourism source markets from 1996Q1 to 2018Q4, we find that not only tourist income and tourism-related relative prices, also visa policies have had significant impacts on Japan's inbound tourism demand in the long run. In the short run, natural disasters have had large and prolonged effects on tourism. We then derive policy implications for the post-COVID-19 revival of Japanese inbound tourism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet